Creep-fatigue crack growth testing and analysis of pre-strained 316H stainless steel - Mehmanparast, Ali; Davies, C. M.; Nikbin, Kamran (Elsevier, 2016)
Material pre-straining is known to have significant effects of the mechanical response and crack growth behaviour of steels. In this paper, the influence of material pre-straining on the subsequent creep-fatigue crack growth behaviour of Type 316H stainless steel at 550 °C has been examined by performing tests on compact tension specimens that were extracted from blocks uniformly pre-compressed at room temperature. Creep-fatigue crack growth tests on pre-compressed material were performed at the frequency of 0.01 Hz and R-ratio of 0.1. The crack growth data obtained from these experiments have been correlated with the C* and K fracture mechanics parameters and the results are compared with the existing creep crack growth data on the pre-compressed and as-received material at 550 °C. The results obtained have also been compared with the creep-fatigue data from experiments on weldments where the crack tip was located in the heat affected zone (HAZ). The crack growth behaviour in creep-fatigue tests on pre-compressed material has been found similar to that of HAZ material and are higher than that of the as-received material. Moreover, depending on the loading condition and frequency the crack growth data obtained from creep-fatigue tests on pre-compressed material may be characterized using C* or ΔK fracture mechanics parameters.
Keywords: Cree-Fatigue interaction; Creep; Fatigue; Crack growth; Stainless steel